EDUKASI PEMAHAMAN KECERDASAN KEMOSIONAL GENERASI Z DI PERGURUAN TINGGI - Budiningtyas, Dwi Putri; Hutabarat, Zuhri (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2025)
This community service activity was carried out to provide a deeper understanding of emotional intelligence to Generation Z students. Based on the situation and problems faced by students of Batanghari Jambi University, the Community Service Team took the initiative to provide education on understanding emotional intelligence for Gen Z students at Batanghari Jambi University. The results of this activity: 1) The ability of Gen Z students to accept, assess, manage, and control their emotions and those of others around them, 2) Emotional intelligence refers to the ability to recognize our own feelings and the feelings of others, and 3) The ability to motivate oneself, and the ability to manage emotions well in oneself and in relationships with others. So it is concluded that this activity can improve the emotional intelligence of Gen Z in preparing themselves to be better.